Alien - Smith, George O. (George Oliver), 1911-1981; Swenson (Salt Lake City, UT : Project Gutenberg, 2022)
"Alien" by George O. Smith is a science fiction novel written in the mid-20th century, specifically in the post-World War II era. The narrative kicks off with the peculiar occurrence of a man with feathers instead of hair, setting the stage for a blend of mystery and humor as the characters navigate the implications of his existence. The book explores themes of alien life and the unusual through a lens of urban police procedural, as Lieutenant Timothy McDowell and others try to make sense of an extraordinary situation. The story follows Lieutenant McDowell as he responds to a riot instigated by a man sporting feathers on his head. Upon investigation, he discovers that the feathers are not merely a costume but rather are growing from the man's scalp, leading to questions about human biology and the possibility of extraterrestrial life. As McDowell and his colleagues delve deeper, they encounter various theories ranging from mutant phenomena due to atomic radiation to actual aliens from outer space. The plot takes an amusing turn as the "feathered man" seeks the help of a follicologist in an attempt to create a publicity stunt revolving around his unique condition. Ultimately, the story combines elements of wit and whimsy with a touch of societal commentary on the nature of fame and identity. (This is an automatically generated summary.)
Release date is 2022-05-29
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Police -- Fiction